(untitled) (CIPEEX, 2025)
Anxiety disorders are among the most common psychiatric conditions, affecting a significant portion of the global population. Pharmacotherapy, especially the use of anxiolytics and antidepressants, is a key component in treating these disorders. However, the improper use of these medications can not only exacerbate symptoms but also lead to dependency. In this context, the pharmacist plays a crucial role, not only in dispensing medications but also in guiding the rational and safe use of these drugs. The active participation of the pharmacist in therapeutic management has been associated with increased treatment adherence and reduced adverse events, highlighting their importance in patient care. This study aims to conduct a bibliographic review on the role of the pharmacist in managing medications for patients with anxiety disorders, focusing on the rational use of anxiolytics and antidepressants and the influence of this intervention on treatment adherence and clinical outcomes. A comprehensive bibliographic review was conducted in the PubMed and Virtual Health Library (BVS) databases. The descriptors used were "patient," "anxiety," "medication," and "pharmacist." The time frame covered the last five years, with articles in English and Portuguese. In BVS, 48 articles were identified, 12 of which were selected after applying the filters. In PubMed, the search returned 2681 results, with 1543 relevant articles selected based on the established criteria. The analysis of the selected articles demonstrated that pharmaceutical interventions in managing medications for patients with anxiety significantly improve treatment adherence while reducing adverse effects and optimizing therapeutic outcomes. Studies indicate that patients who receive pharmaceutical guidance experience fewer side effects and greater satisfaction with their treatment. Pharmacogenomics emerged as a promising approach for personalizing antidepressant therapy, especially relevant in community pharmacy settings. The pharmacist’s role in managing medication therapy for patients with anxiety is essential for promoting the rational use of medications and improving clinical outcomes. Personalized treatment, combined with proper pharmaceutical guidance, contributes to improved patient quality of life and mitigates complications arising from the improper use of anxiolytics and antidepressants.